Adaptation of farmland management strategies to maintain livelihood by the Chagga people in the Kilimanjaro highlands. (May 2020) - Ichinose, Yuri; Higuchi, Hirokazu; Kubo, Ryosuke; Nishigaki, Tomohiro; Kilasara, Method; Shinjo, Hitoshi; Funakawa, Shinya
Abstract: Smallholder farmers attempt to adapt their farmland management through multiple strategies in order to secure their livelihood against external stress factors. Cultivating different species and genotypes of crops is one of the strategies implemented by smallholder farmers to maintain their livelihood. In the Kilimanjaro highlands, the Chagga people run small-scale farming. Traditionally, they cultivate diverse varieties of banana and coffee in home gardens in high-altitude areas and maize in low-altitude foothill farms. However, this type of farmland management had to be altered gradually in response to changes in external factors. This paper examines the role of cropping practice and diverse banana genotypes in the livelihood of the Chagga people, to understand how they altered their farmland management strategy to adapt to the current socio-economic circumstances, based on interviews, observations, and genetic analysis of banana. Our results showed that the Chagga people had altered their farmland management strategy by increasing banana and maize cultivation and decreasing coffee cultivation in the home garden based on the significance of each crop in their livelihood. The importance of banana cultivation for the livelihood of Chagga people has been recently recognized as an income source in addition to a staple food because of its increasing demand in neighboring big cities. Maize cultivation in home gardens has expanded because of the steady increase in the household demand of maize over the last 40 years and the decrease in size and ownership of foothill farms. Conversely, coffee cultivation as a household income has declined because of a reduction in coffee prices in the world market and increasing challenges in its cultivation. Additionally, the Chagga people accurately distinguish and use 11 types of bananas in their daily diet and cultural use. Maintaining diverse genotypes of bananas in home gardens is one of the adaptation strategies that bring stable food supply and income, and consequently enable them to maintain their livelihood under changing socio-economic circumstances. Highlights: Optimizing crop species is the adaptation strategy of farmland management. Significance of crops in the livelihood determines the choice of crop species. Preserving diverse genotypes of bananas has contributed to food security.